Development of a Mental Health Screening Website Akubahagia.com to Prevent Adolescent Mental Health Disorders - Melawati, Ayu; Yuhana, Yuyu; Atikah, Cucu (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2026)
Abstract: Mental health disorders among adolescents are on the rise, with many struggling to cope with everyday challenges, leading to depression, anxiety, and stress. This situation highlights the lack of optimal promotive and preventive mental health efforts. As a preventive initiative, this study aims to develop and validate a mental health screening website. The research employed the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model of development. The website was created using HTML, PHP, JavaScript, CSS, and MariaDB, and was tested through expert validation and field implementation. Media and content experts conducted validation tests, followed by a small-scale trial and a large-scale trial involving users aged 11–18. Results showed that the website received a feasibility rating of 71% from media experts and 91.7% from content experts. Field testing yielded an average user rating of 85%, with sub-aspect scores of 90% for effectiveness, 91% for practicality, 86% for attractiveness, and 83% for feasibility. These findings indicate that Akubahagia.com is highly suitable for use in early detection and prevention of mental health disorders among adolescents. Abstrak: Gangguan kesehatan mental di kalangan remaja semakin meningkat, dengan banyak di antara mereka yang kesulitan mengatasi tantangan sehari-hari, yang berujung pada depresi, kecemasan, dan stres. Situasi ini menyoroti kurangnya upaya promosi dan pencegahan kesehatan mental yang optimal. Sebagai inisiatif pencegahan, penelitian ini bertujuan untuk mengembangkan dan memvalidasi sebuah situs web skrining kesehatan mental. Penelitian ini menggunakan model pengembangan ADDIE (Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi). Situs web tersebut dibuat menggunakan HTML, PHP, JavaScript, CSS, dan MariaDB, serta diuji melalui validasi ahli dan implementasi lapangan. Para ahli media dan konten melakukan uji validasi, diikuti dengan uji coba skala kecil dan uji coba skala besar yang melibatkan pengguna berusia 11–18 tahun. Hasil menunjukkan bahwa situs web tersebut memperoleh penilaian kelayakan sebesar 71% dari para ahli media dan 91,7% dari para ahli konten. Pengujian lapangan menghasilkan penilaian rata-rata pengguna sebesar 85%, dengan skor sub-aspek sebesar 90% untuk efektivitas, 91% untuk kepraktisan, 86% untuk daya tarik, dan 83% untuk kelayakan. Temuan ini menunjukkan bahwa Akubahagia.com sangat cocok untuk digunakan dalam deteksi dini dan pencegahan gangguan kesehatan mental di kalangan remaja.